2020
DOI: 10.1055/s-0040-1710010
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 as a Biomarker of Early-Onset Neonatal Sepsis

Abstract: Objective The aim of this study is to determine the utility of C reactive protein (CRP) and interleukin (IL)-6 in the diagnosis of neonatal sepsis (NS) in a neonatal intensive care unit (NICU) in the south of Colombia. Study Design A nonmatched case–control study was conducted. Convenience sampling was performed. Data were obtained from clinical records. IL-6 levels were determined using enzyme-linked immunosorbent assay. Receiver operator characteristic (ROC) curve analysis and Youden's index were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The analysis of IL-6 concentrations showed a strong predictive value for neonatal sepsis (both EOS and LOS). Our data favor a cut-off value at 100 ng/L, while different cut-off values have been suggested by others [ 25 , 26 , 27 , 28 , 29 , 30 ]. The sensitivity and specificity at this cut-off value showed similar results to those published in 2018 by the Association of the Scientific Medical Societies in Germany (AWMF) [ 6 , 26 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 57%
“…The analysis of IL-6 concentrations showed a strong predictive value for neonatal sepsis (both EOS and LOS). Our data favor a cut-off value at 100 ng/L, while different cut-off values have been suggested by others [ 25 , 26 , 27 , 28 , 29 , 30 ]. The sensitivity and specificity at this cut-off value showed similar results to those published in 2018 by the Association of the Scientific Medical Societies in Germany (AWMF) [ 6 , 26 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 57%
“…First clinical studies using CRP as biomarker to detect bacterial infections were performed in the late 1980s, and CRP was used in the 1990s for detection of septic neonates showing promising clinical usage of CRP for diagnosis of neonatal sepsis [ 36 , 37 , 38 , 39 ]. The most recent study correlating neonatal sepsis with elevated levels of CRP and IL-6 was published by Cortes et al and demonstrated that CRP could be a useful biomarker in combination with other inflammatory biomarkers, especially for late-onset neonatal sepsis [ 40 ]. Recently, 14 clinical studies were summarized by Pay and Shaw [ 41 ] ) showing a correlation of salivary CRP and serum CRP levels with R 2 of 0.53 ± 0.23, comparable to the result of our study with a R 2 value of 0.52 ( Figure 1 A).…”
Section: Discussionmentioning
confidence: 99%
“…Even though clinical studies linked salivary CRP positively as a marker for metabolic syndrome [ 42 ], detection of obesity in children [ 43 ], or pneumonia in neonates [ 17 ], a study published in 2019 with 37 healthy young males showed no clear correlation between salivary and serum concentrations of CRP [ 44 ]. Additionally, even though CRP is commonly used as a marker for neonatal sepsis, recent clinical studies claimed the need of other salivary markers for diagnosis due to unreliable screening validity of salivary CRP [ 18 , 19 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cortes et al evaluated diagnostic accuracy of IL-6 and CRP in EOS and LOS 104 . Authors concluded that IL-6 (>17.75 pg/mL) showed greater accuracy in EOS while CRP (>0.53 mg/dL) was more accurate in LOS.…”
Section: Current Methods To Diagnose Neonatal Sepsismentioning
confidence: 99%